Understanding internet addiction and its associated factors among children and adolescents : a review of literature - Ayuzeity Bistari Md Bukhorii,; Mohd. Hasni Ja’afar, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Internet Addiction (IA) is becoming increasingly recognized as a serious public health issue, particularly for children and adolescents. This review article discussed the complexity of IA diagnostic criteria and IA-related risk factors from a public health perspective with the intention of fostering a better understanding of IA in adolescents and children. The entire discussion pointed out how the epidemiological triad of disease framework helps to explain the IA associated factors among adolescents. This framework emphasises the agent (Internet characteristics and its content), host (e.g., self-personality, comorbidity, psychological status, inter- and intrapersonal relationship), and environment as extrinsic factors (i.e., physical pollution, socioeconomic status, availability, and accessibility of the Internet) that facilitate interaction between the agent and the host. Evaluation of all three components and their association with IA is essential as it allows for a more comprehensive understanding of how the issues arise, which can be useful in developing future effective public health measures for IA.